Clinical approach to chronic wound management in older adults. Issue 8 (17th May 2021) - Alam, Wahila; Hasson, Jonathan; Reed, May
Abstract: Older adults are at high risk of developing chronic wounds due to numerous changes that occur with aging. It is reasonable to consider chronic wounds as a geriatric syndrome—highly prevalent, multifactorial, and associated with substantial morbidity and mortality. Due to the morbidity and cost associated with chronic wounds, prevention, early diagnosis, and treatment are important. The most common chronic wounds presenting in older adults are pressure and vascular wounds, including those associated with diabetes. Atypical wounds are also common and should raise the suspicion for skin malignancy. Diagnosis is primarily clinical and assessment should include documentation of wound characteristics, such as location, size and depth, presence of slough, drainage, odor, and infection. The mainstay of treatment is based on the TIME principle: T issue debridement, I nfection control, M oisture balance, and optimal wound E dges. The use of protein supplements has been shown to improve wound healing in subsets of older adults. In addition to wound care and optimizing nutrition, disease‐specific wound therapy forms an integral part of wound management. Pressure reduction for pressure injury, compression therapy for venous wounds, evaluation of arterial circulation with ABI or arterial Doppler and iCC for diabetic ulcers form the mainstays of therapy. Atypical wounds may present as chronic ulcers and should be biopsied. The goals of treatment should be realistic and for some older adults, palliative wound management may be more appropriate.